Risk Factors for Infection with Soil Transmitted Helminths, Cryptosporidium spp., and Giardia duodenalis in Children Enrolled in Preschools in Kafue District, Zambia. (1st April 2015) - Siwila, Joyce; Olsen, Annette
Abstract : Intestinal parasitic infections are common among children worldwide. This study was aimed at determining risk factors for infection with soil transmitted helminths, Cryptosporidium spp., and Giardia duodenalis, among children in preschools. The study was in two parts: a cross-sectional study in which data were collected from 403 children from 10 preschools and a longitudinal study in which 100 children from four preschools from the previous 10 were selected. Prevalence of Ascaris lumbricoides was 12.0%, while that of hookworm was 8.3%. Overall prevalence of Cryptosporidium and G. duodenalis was 28.0% and 29.0%, respectively. Low education level of parent/guardian was a significant risk factor for A. lumbricoides (OR = 2.35, 95% CI: 1.02–5.41;P = 0 . 04 ), while roofing types other than corrugated iron sheets were found to be protective for G. duodenalis infection in both bivariate and multivariate analyses (multivariate: OR = 0.67, 95% CI: 0.45–0.99;P = 0 . 04 ). Low socioeconomic level was found to be protective for Cryptosporidium spp. infection in multivariate analysis (OR = 0.59, 95% CI: 0.35–0.99;P = 0 . 04 ). In the longitudinal study, none of the factors were associated with either infection. These findings may have implications for other preschools in other districts in Zambia.